New insights in the low-temperature-dependent formation of amorphous titania-coated magnetic polydopamine nanocomposites for the adsorption of methylene blue - Jiangqun Zhang; Xingyu Long; Meng Hu; Wanli Wei; Jiangning Gong; Chun Yang; Pinhua Xia; Anping Wang (Scientific Reports)
Abstract Removal of accumulated dyes from the environment water bodies is essential to prevent further harm to humans. The development and design of new alternative nanoadsorbents that can conveniently, quickly, and efficiently improve the adsorption and removal efficiency of dyes from wastewater remains a huge challenge. An amorphous TiO2 with a magnetic core-shell-shell structure (Fe3O4@PDA@a-TiO2, denoted as FPaT) was constructed through a series of steps. The studies on the formation mechanism of FPaT indicated that the reaction temperature was the most important parameter affecting crystal structure. To analyze the magnetic properties of the core, the amorphous structure of the shell, and the surface properties (size and morphology, elemental composition, functional groups, crystal structure, magnetic properties, etc.) of FPaT, various analytical techniques including scanning electronic microscopy (SEM), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD) and vibrating sample magnetometer (VSM) were utilized to characterize it. Based on the unique physicochemical properties of its surface, the FPaT was applied to highly adsorb methylene blue (MB) from simulated wastewater. Furthermore, batch adsorption experiments towards MB were performed to assess the high adsorption ability and reusability of the prepared FPaT. Using 4.5 mg of FPaT to adsorb MB solution with an initial concentration of 10 mg/L (pH = 8.2), 97% adsorption rate was achieved within 30 min. Compared with the previously reported values of other absorbent materials, the maximum adsorption capacity (313.7 mg/g) is much higher. The equilibrium adsorptions and the adsorption kinetic data were better depicted by the Langmuir isothermal adsorption model (R 2 = 0.943) and by a second-order kinetic model (R 2 = 0.999), respectively. In conclusion, this work indicates that FPaT, as a novel adsorbent, has good application prospects for removing MB from actual dye wastewater.